Energy‐efficient switching method for SAR ADCs with bottom plate sampling. Issue 9 (4th April 2016) - Zhang, Yulin; Bonizzoni, Edoardo; Maloberti, Franco
Abstract : A high energy‐efficiency capacitor switching scheme for successive approximation register (SAR) analogue‐to‐digital converters (ADCs) is presented. The switching method, verified on a 10‐bit SAR scheme that uses bottom plate sampling, achieves an average switching energy and area reduction of 99.32 and 96.5%, respectively, with respect to the conventional solution.